Potensi Singkong Sebagai Alternatif Beras Menjunjung Diversifikasi Pangan Nasional: Pengaplikasian Singkong Sebagai Bahan Pokok Kampung Adat Cireundeu - Qinthara, Fayyaadh; Kusuma, Finna Najwa Dwi; Dzahabiyah, Syahla Azizah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The human need for food is crucial for survival. Food diversification is the right step to achieve food security and improve welfare. Sources of carbohydrates are the main needs that people need every day, while the demand for rice and the availability of rice are not comparable. Cassava as a food that is rich in carbohydrates, vitamins, and minerals needs to be optimized so that Indonesian people do not depend on just one type of food. In addition to improving food security, food diversification can also benefit the agricultural economic sector and improve farmers' welfare. Cirendeu Traditional Village is an inspiring example of food diversification. They made cassava a staple and succeeded in improving the economy with various innovations. So that the people there do not have to worry about the current food crisis. Cireundeu shows that food diversification on a national scale is essential for long-term food security. We need to adapt to other sources of carbohydrates and develop innovations to increase their value and utilization. Food diversification is not only about food security but also about economic opportunities and community welfare.